O desafio da tutela sanitária e ambiental na área de saneamento básico: análise do caso de abastecimento de água e esgotamento sanitário do Estado do Amapá - Nascimento, Adilson Garcia do (2016)
This thesis is to point of interest a discussion of the causes of ineffectiveness of health and environmental protection in the distribution area of water and sanitation, focusing on the emblematic case of low rates in the industry in the State of Amapá, as well as analysis of the framework environmental legal guardian of the right to sanitation. To accomplish this research, it became the route of the process of historical development of basic sanitation in Brazil. Therefore, seeks to show that the country has enough laws, but suffers the implementation thereof. Then they made up some considerations on the sectoral public policies, these judicial activism and the advantages and disadvantages of legalization as a means of conflict resolution, including the provision of reservation possible. Thus, it can be said that that approach gives prominence to the debate about linking sanitation to public health. It is noteworthy that were not ignored important points for the universal service, such as the restructuring plan as a management tool, mishaps and prospects in its preparation, with the analysis of public policy under the bias of the executive. They were further analyzed the technical indexes of basic sanitation in the State of Amapá, with your data and features. This research helps confirm partially the hypotheses formulated for this research, namely: environmental protection and health is ineffective in basic sanitation, by exogenous legal factors, although they were identified endogenous causes the legal harvest